Expression of fibulin-6 in failing hearts and its role for cardiac fibroblast migration. (20th June 2014) - Chowdhury, Arpita; Herzog, Christine; Hasselbach, Lisa; Loghmani Khouzani, Houra; Zhang, Jinli; Hammerschmidt, Matthias; Rudat, Carsten; Kispert, Andreas; Gaestel, Matthias; Menon, Manoj B.; Tudorache, Igor; Hilfiker-Kleiner, Denise; et al.
Abstract: Aims: The cardiac extracellular matrix (ECM) undergoes a dynamic transition following myocardial infarction. Fibulin-6 is expressed in cell junctions particularly in tissues subjected to significant mechanical stress. Fibulin-6 deficiency results in defective cell migration in nematodes and early embryonic lethality in mice. The role of fibulin-6 in healthy and failing myocardium is unknown. We have examined the expression and distribution pattern of fibulin-6 during myocardial remodelling (MR) and detailed its effect on the migratory function of cardiac fibroblasts (CFs) in response to TGF-β1. Methods and results: In healthy murine myocardium, fibulin-6 expression is largely confined to larger coronary arteries. It is induced during the early and the late phase of remodelling after infarction in murine hearts predominantly in the scar–muscle junction. Similar results are obtained in human ischaemic cardiomyopathy. Fibulin-6 is mostly expressed in close vicinity to vimentin-positive cells and is also abundantly expressed in vitro in cultured neonatal CF. TGF-β1 does not induce smooth muscle actin in fibroblasts deficient of fibulin-6, which also compromised their migration. Cells that had migrated expressed more fibulin-6 compared with stationary cells. Plated on fibulin-6-depleted matrix, stress fibre induction in fibroblast in response to TGF-β1 was impaired. In e x vivo explant cultures from post-infarct myocardium, the number of emigrating fibroblasts was also significantly reduced by fibulin-6 siRNA knockdown. Conclusion: Fibulin-6, a fibroblast-released ECM protein, may play an important role during MR by imparting an effect on CF migration in close and complementary interplay with TGF-β1 signalling.